MANUSIA SEBAGAI MAKHLUK YANG PERLU DAN DAPAT DIDIDIK - Fadhilah, Izza Amirul; Maunah, Binti (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2021)
Abstract: The purpose of writing this journal is to describe and know that humans are creatures who need and can be educated. The method used is library research that collects and/or explores various journals, books and documents (both printed and electronic). Humans themselves are born as helpless humans, who do not yet have the ability to adapt to their environment, so humans need to be educated. And also humans can be educated in a learning process that takes a long time to adjust to their environment or is often educated. Through education, humans can develop and adapt to their environment. Education introduces people to science and technology. In other words. Through education, humans can maximize the potential that exists in themselves.